Successful Treatment of Congenital Hyperinsulinism Due to KJNJ11 Gene Mutation with Long-Acting Release Octreotide: A Case Report from the Arab Region - Hasan, Gamal M.; Al Hakim, Ammar; Eldesoky, Mohammad; Suleman, Iftikhar; Deeb, Asma (Journal of Diabetes and Endocrine Practice, 2023)
Congenital hyperinsulinism is a rare hereditary condition that is caused by various gene mutations related to the function of the pancreatic β-cells. It is characterized by dysregulation of insulin secretion leading to profound and recurrent hypoglycemia. Its clinical presentation, histology, response to treatment, and underlying genetic defects are variable making it a heterogeneous condition. Pancreatectomy is indicated in diazoxide un-responsive cases. However, surgical treatment is associated with the possibility of persistent hypoglycemia and iatrogenic diabetes. We report a 3 months old girl who presented with hyperinsulinemic hypoglycemia. She was born to consanguineous parents and had a history of four neonatal deaths in siblings. Whole exome sequencing detected a KCNJ11 variant c.350_352del p.(Phe117del) in a homozygous state. Pancreatic scan (positron emission tomography/computed tomography) showed a diffusely increased radioisotope uptake in the head and tail of the pancreas. She was resistant to diazoxide and nifedipine and was shifted to octreotide treatment through multiple daily subcutaneous injections initially. Treatment was changed to monthly depot injection of octreotide that resulted in euglycemia. She kept a normal rate of growth, insulin-like growth factor-1, and liver function. This case is an example of an alternative effective medical therapy that avoids major surgical intervention and prevents long-term complication of recurrent hypoglycemia and iatrogenic diabetes resulting after surgery.
Keywords: congenital hyperinsulinism; KCNJ11; hypoglycemia; octreotide